2020
DOI: 10.1111/gcbb.12667
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of genetic markers for sex and cannabinoid chemotype in Cannabis sativa L.

Abstract: Hemp (Cannabis sativa L.) is an emerging dioecious crop grown primarily for grain, fiber, and cannabinoids. There is good evidence for medicinal benefits of the most abundant cannabinoid in hemp, cannabidiol (CBD). For CBD production, female plants producing CBD but not tetrahydrocannabinol (THC) are desired. We developed and validated high‐throughput PACE (PCR Allele Competitive Extension) assays for C. sativa plant sex and cannabinoid chemotype. The sex assay was validated across a wide range of germplasm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 52 publications
8
77
3
2
Order By: Relevance
“…Although environmental factors play a role in determining the amount of cannabinoids present in different parts and stages of the plant (Rustichelli et al 1998), in most populations the ratio between THCA and CBDA has been found to be under genetic control (Mandolino et al 2003;Weiblen et al 2015;Toth et al 2020;Wenger et al 2020). Codominant inheritance of CBDA and THCA chemotypes is consistent with a Mendelian single-locus (de Onofri et al 2015;Weiblen et al 2015).…”
Section: Cannabinoid Oxidocyclase Gene Evolutionmentioning
confidence: 91%
“…Although environmental factors play a role in determining the amount of cannabinoids present in different parts and stages of the plant (Rustichelli et al 1998), in most populations the ratio between THCA and CBDA has been found to be under genetic control (Mandolino et al 2003;Weiblen et al 2015;Toth et al 2020;Wenger et al 2020). Codominant inheritance of CBDA and THCA chemotypes is consistent with a Mendelian single-locus (de Onofri et al 2015;Weiblen et al 2015).…”
Section: Cannabinoid Oxidocyclase Gene Evolutionmentioning
confidence: 91%
“…Rotherham and Harbison (2011) reported a set of single nucleotide polymorphism (SNP) markers based on differences between “drug‐type” and “fiber‐type” THCAS (Kojoma et al, 2006), but the latter THCAS sequence was reclassified by Laverty et al (2019) as cannabichromenic acid synthase ( CBCAS ). These SNP markers and others derived from THCAS sequence (Staginnus et al, 2014) can distinguish THC‐type and CBD‐type plants, but they fail to differentiate THC‐type from intermediate‐type plants (Toth et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…Plants that are heterozygous at the CBDAS locus have the intermediate type. The opportunity to test the validity of the model and its utility for predictive genotyping has only recently emerged with greater access to diverse populations of C. sativa (Toth et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…Recently, others have proposed targeted markers for the identification of fiber and resin cannabis (e.g. Cascini et al 2019 ; Hilyard et al 2019 ) as well as molecular sexing tools to differentiate feminized from regular seed stock (Toth et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%